IAPs Gene Expansion in the Scallop Patinopecten yessoensis and Their Expression Profiles After Exposure to the Toxic Dinoflagellate - Zhu, Xiaomei; Zhang, Fengmei; Lian, Shanshan; Wang, Yinghui; Hu, Naina; Chen, Xiaomei; Dai, Xiaoting; Hu, Xiaoli; Wang, Shi; Bao, Zhenmin (Frontiers in Physiology, 2021)
Inhibitors of apoptosis proteins (IAPs) are conserved regulators involved in cell cycle, cell migration, cell death, immunity and inflammation, due to which they can assist with the ability to cope with different kinds of extrinsic or intrinsic stresses. Bivalve molluscs are well adapted to highly complex marine environments. As free-living filter feeders that may feed on toxic dinoflagellates, bivalves can accumulate and tolerate high levels of paralytic shellfish toxins (PSTs), from which the toxic stress will be induced and causing deleterious effects. Here, we systematically analyzed IAP genes (PyIAPs) in Yesso scallop (Patinopecten yessoensis), an important fishery and aquaculture species in China. Forty-seven PyIAPs from five sub-families were identified, and almost half of the PyIAP genes were localized in clusters on two chromosomes. Significant expansion of sub-families BIRC4 and BIRC5 that under the pressure of purifying selection was revealed. After exposure to PST-producing dinoflagellates, Alexandrium catenella, fourteen PyIAPs showed significant responses in hepatopancreas and kidney, and more than eighty-five percent of them were from the expanded sub-families BIRC4 and BIRC5. The regulation pattern of PyIAPs was similar between the two tissues, with more than half exhibited expression suppression within three days after exposure. While in comparison with hepatopancreas, more acute changes of PyIAPs expression could be detected in kidney, suggesting the possible involvement of these PyIAPs in tissue-specific PST tolerance. These findings also imply the adaptive expansion of bivalve IAP genes in responding to algae derived biotoxins.